The Practicality and Effectiveness of Educational Game Developed using Lectora Inspire in Chemical Equilibrium - Hidayani, Rahmah; Sabekti, Ardi Widhia; Yulita, Inelda (JCER (Journal of Chemistry Education Research), 2020)
The aim of this study was to determine the practicality and effectiveness of educational game media using the Lectora Inspire application on chemical equilibrium. This study used research and development (R&D) methods, with the ADDIE research model, namely Analysis, Design, Development, Implementation, and Evaluation. In this study only the Implementation and Evaluation stage was carried out. The test subjects in this study were 2 teachers and 20 students of class XI IPA 2 Madrasah Aliyah Negeri Tanjungpinang. The results of practicality tests using teacher questionnaire responses was 88% with the category of very practical and in terms of student responses, it was obtained a percentage of 84% with very practical criteria. In the aspect of effectiveness obtained learning outcomes with pretest and posttest scores N-Gain 0.5 results in the medium category. Based on the results of evaluations conducted by educative game media using the Lectora Inspire application on chemical equilibrium, it is declared practical, and effective for use.